Disegno and Design. Declensions of Terms and Practices Actualizations (diségno, 2022)
“It is interesting to think about the relationship between drawing and design, and about the role of drawing in design: this is almost a play on words, but –as often happens– playing can lead us to reflect more deeply. On English-language design courses, the word ‘design’ is almost always accompanied by another term to specify the field in question: furniture design, car design, lighting design, and so forth. It is perhaps not very well-known, however; that the word ‘design’ actually derives from the Italian word ‘disegno’, meaning ‘drawing’, which in turn derives from the Latin ‘design-are’” [Pasca 2010, p. 12]. With this introduction, in the essay Drawing and Design, Vanni Pasca in 2010 questioned the positioning of sketching and, more generally, analog drawing as a suitable practice for transmitting a conceptual reflection irreplaceable of project: the manifestation of the idea. [read more]